Structure and functional dynamics of the mitochondrial Fe/S cluster synthesis complex - Michal T. Boniecki (Nature Portfolio, 2017)
Fe/S clusters are synthesized by the mitochondrial iron-sulfur cluster assembly (ISC) machinery. Here the authors combine crystallography and small angle X-ray scattering measurements to structurally characterize the core ISC complex and give functional insights into eukaryotic Fe/S cluster synthesis.